2015
DOI: 10.1093/mnras/stv714
|View full text |Cite
|
Sign up to set email alerts
|

Short versus long gamma-ray bursts: a comprehensive study of energetics and prompt gamma-ray correlations

Abstract: We present the results of a comprehensive study of the luminosity function, energetics, prompt gamma-ray correlations, and classification methodology of short-hard and long-soft GRBs (SGRBs & LGRBs), based on observational data in the largest catalog of GRBs available to this date: BATSE catalog of 2702 GRBs. We find that: 1. The least-biased classification method of GRBs into short and long, solely based on prompt-emission properties, appears to be the ratio of the observed spectral peak energy to the observe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 119 publications
(206 reference statements)
4
69
0
Order By: Relevance
“…Attempts of using the combination of E p , E iso , T 90,i parameters and Amati relation as classification discriminators were made in several papers (e.g. Lü et al 2010;Qin & Chen 2013;Zhang et al 2018b;Shahmoradi & Nemiroff 2015;Zou et al 2018;Pozanenko et al 2018). Below we briefly compare the several classification schemes.…”
Section: Comparison With Several Other Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Attempts of using the combination of E p , E iso , T 90,i parameters and Amati relation as classification discriminators were made in several papers (e.g. Lü et al 2010;Qin & Chen 2013;Zhang et al 2018b;Shahmoradi & Nemiroff 2015;Zou et al 2018;Pozanenko et al 2018). Below we briefly compare the several classification schemes.…”
Section: Comparison With Several Other Classificationmentioning
confidence: 99%
“…In Shahmoradi & Nemiroff (2015) the classification parameter R = E p /T 90 was proposed as least affected parameter by the detection threshold of gamma-ray detectors. It was also suggested, that the two GRB types are most distinctively separated in the E p -T 90 plane.…”
Section: Comparison With Several Other Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…3.19). However, we know from observations that the low-energy component (i.e., for E γ < E γ,b ) is harder for sGRBs than for the long-duration GRBs (see the values for α γ in Table 1) and the peak energy is slightly higher [61][62][63].…”
Section: Short-duration Gamma-ray Burstsmentioning
confidence: 99%
“…Kouveliotou et al (1993) also found a bimodal structure in the log T 90 distribution of 222 events from CGRO/BATSE, based on which GRBs are commonly divided into short (T 90 < 2 s) and long (T 90 > 2 s) classes, where T 90 is the time interval from 5 % to 95 % of the accumulated fluence. While generally short GRBs are of merger origin (Nakar 2007) and long ones come from collapsars (Woosley and Bloom 2006), this classification is imperfect due to a large overlap in duration distributions of the two populations (Lü et al 2010;Bromberg et al 2011Bromberg et al , 2013Shahmoradi 2013;Shahmoradi and Nemiroff 2015;Tarnopolski 2015c). Horváth (1998) and Mukherjee et al (1998) independently discovered a third peak in the duration distribution in the BATSE 3B catalog, located between the short and long groups, and the statistical existence of this intermediate class was claimed to be supported (Horváth 2002) with the use of BATSE 4B data.…”
Section: Introductionmentioning
confidence: 99%